Usefulness of cardiac biomarker screening to detect dilated cardiomyopathy in Dobermanns. (13th December 2021) - Dukes‐McEwan, J.; Garven, K. E.; Lopez Alvarez, J.; Oliveira, P.; Motskula, P. F.; Willis, R.
Abstract : Objectives: To assess the diagnostic accuracy of two cardiac biomarker assays (N‐terminal pro‐BNP, Troponin I) in detecting dilated cardiomyopathy in Dobermanns. Materials and Methods: Dobermanns undergoing cardiac biomarker testing were screened by echocardiography and Holter monitoring, then assigned to a group: normal, equivocal, arrhythmia form of dilated cardiomyopathy, echocardiographic form of dilated cardiomyopathy or both. Some were reassessed to identify final status. Initial cardiac biomarker results were compared to final status. Receiver operating characteristic curves were used to identify area under the curve and corresponding sensitivity (Se), specificity (Sp) for different cut‐offs (CO) for each cardiac biomarker. Results: A total of 118 Dobermanns with cardiac biomarker data had echocardiography/Holter assessment. Repeat assessment was carried out in 47 Dobermanns after 394.5 ±151.0 days. Seventeen dogs changed group between initial and final status. The final status of 59 was normal, nine were equivocal and 50 had dilated cardiomyopathy (prevalence 42.4%). Of the dilated cardiomyopathy group, 25 had dilated cardiomyopathy‐both, 13 dilated cardiomyopathy‐echocardiography and 12 dilated cardiomyopathy‐Holter. Receiver operating characteristic area under the curve=0.807 for N‐terminal proBNP (Se 0.69 and Sp 0.81) and 0.873 for high‐sensitivity cardiac Troponin I (Se 0.77 and Sp 0.86). When both Se and Sp were optimised for all forms of dilated cardiomyopathy, N‐terminal proBNP cut‐off was 626 pmol/L (Se and Sp 0.79) and high‐sensitivity cardiac Troponin I cut‐off was 0.056 ng/mL (Se and Sp 0.84). Receiver operating characteristic area under the curve was higher for dilated cardiomyopathy‐echocardiography (NT‐proBNP 0.883; high‐sensitivity cardiac Troponin I 0.907) than dilated cardiomyopathy‐Holter. Clinical Significance: Cardiac biomarker screening may be useful to select Dobermanns which would benefit from further assessment by echocardiography and Holter.